Gardens of Transylvanian manor estates I. - Fekete, Albert (4D Journal of Landscape Architecture and Garden Art, 2006)
Certain stylistic periods in garden history appearing in Hungary cannot be comprehended without the mementos of Transylvanian garden design. One such period is the late Renaissance, when due to the cultural break in Hungárián territories under Turkish reign, Transylvania along with Western Hungary became the last bastions of eontinuity of our matérial and immaterial heritage.